Exploring the patient perspectives of mobile X-ray in nursing homes – A qualitative explorative pilot study. Issue 2 (May 2021) - Jensen, J.M.; Andersen, P.A.B.; Kirkegaard, L.; Larsen, N.; Most, W.; Nielsen, D.; Precht, H.
Abstract: Introduction: For patients with dementia, behaviour and reactions to stimuli can change and an X-ray examination in the hospital can have be a frightening experience. The aim of this study was to identify the experiences and perspectives of patients with dementia and their caregivers on receiving a mobile x-ray examination in nursing homes. Methods: This study was designed as a qualitative study using patient observation and semi structured interviews, with a phenomenology-hermeneutic approach. In total, 23 patients were observed during X-ray examinations in nursing homes, and six semi structured interviews were conducted with the caregivers who participated in the examination. Results: The observations and interviews indicated that a known environment, a recognizable framework and calmness were central for a patient with dementia. The patients appeared calm and relaxed during the examination in their usual environment (nursing homes) where there are less stimuli and impressions based of the observations. Conclusion: Mobile X-ray examinations for patients with dementia living in nursing homes had a positive impact on patients' reactions towards the X-ray examination. The examinations were performed in the patients' usual and safe environments, where impressions and stimuli were less disturbing for patients with dementia. Implications for practice: The mobile x-ray unit can be of benefit for patients suffering from dementia and result in less impact. The patients living in nursing homes have the opportunity to be examined in their familiar environment, because of the mobile x-ray unit.